2011
DOI: 10.1016/j.vaccine.2011.04.119
|View full text |Cite
|
Sign up to set email alerts
|

A pandemic influenza vaccine in India: From strain to sale within 12 months

Abstract: In the event of a highly pathogenic influenza pandemic, the Indian subcontinent would need 1.2 billion doses of vaccine to immunize its entire population, double if two doses were required to assure immunity. Serum Institute of India Limited (SII) thus became one of six initial grantees of the World Health Organization (WHO) technology transfer initiative to create capacity in developing countries to manufacture H5N1 pandemic influenza vaccine. At the outbreak of the A(H1N1) 2009 influenza pandemic, experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…40 As a result, many countries have already established influenza vaccine manufacturing capabilities and some used locally produced vaccines during the 2009 pandemic. 41,42 Furthermore, a recent pilot programme of influenza vaccination in the Lao People's Democratic Republic demonstrated that public-private partnerships can improve vaccination programmes in developing countries. 43 The data reported here have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…40 As a result, many countries have already established influenza vaccine manufacturing capabilities and some used locally produced vaccines during the 2009 pandemic. 41,42 Furthermore, a recent pilot programme of influenza vaccination in the Lao People's Democratic Republic demonstrated that public-private partnerships can improve vaccination programmes in developing countries. 43 The data reported here have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…122 No serious side effects have been reported associated with the administration of Nasovac indicating its safety, 123 although its efficacy data are not sufficiently available yet. 124 Until recently FluMist was considered one of the most successful intranasal vaccines, it is well tolerated and had exhibited good efficacy. 125 A runny nose/nasal congestion has been reported as the most common adverse events of Flumist, with mild to moderate in severity.…”
Section: Current Nasal Vaccine Productsmentioning
confidence: 99%
“…9 After immunogenicity and safety was demonstrated in clinical studies (Prasad S Kulkarni, unpublished data), 10 the vaccine was licensed by the Drug Controller General of India (DCGI) on 3 July 2010. One intra-nasal dose of 0.5 ml was recommended for adults and children ≥3 y of age.…”
Section: Introductionmentioning
confidence: 99%